Cell‐free DNA analysis of maternal blood in prenatal screening for chromosomal microdeletions and microduplications: a systematic review. (12th March 2021) - Familiari, Alessandra; Boito, Simona; Rembouskos, Georgios; Ischia, Benedetta; Accurti, Veronica; Fabietti, Isabella; Volpe, Paolo; Persico, Nicola
Abstract: Background and aim of the study: Scientific Societies do not recommend the use of cell‐free DNA (cfDNA) testing as a first‐tier screening for microdeletion and microduplication syndromes (MMs). The aim of this study was to review the current available literature on the performance of cell‐free DNA as a screening for MMs. Methods: Medline, Embase and the Cochrane Library were searched electronically from 2000 to January 2020 and articles reporting the diagnostic performance of cfDNA screening for MMs in large (>5000 cases) series were included. Between‐study heterogeneity and random effect model for screen positive rate (SPR), false positive rate (FPR) and positive predictive value (PPV) were calculated. Results: We identified 42 papers, seven included, for a total of 474, 189 pregnancies and 210 cases of MMs. Diagnostic verification of positive cases was available overall in 486 (71.68 %) of 678 cases. The weighted pooled SPR, FPR and PPV were 0.19% (95% CI = 0.09–0.33), 0.07 (95% CI = 0.02–0.15) and 44.1 (95% CI = 31.49–63.07). In conclusion, the pooled PPV of cfDNA testing in screening for MMs was about 40%, ranging from 29% to 91%, for an overall FPR <0.1%. Conclusions: No confirmatory analysis was available in cases that did not undergo invasive testing, which were the vast majority of cases with a negative test, and therefore, the DR and the negative predictive value cannot be determined. Key Points: What's already known about this topic? Cell‐free DNA (cfDNA) as screening test for microduplication (MMs) is burdened by a high variability of positive predictive value (PPV) which is far from being considered acceptable. Scientific Societies worldwide are concordant in recommending not to offer cfDNA testing for MMs outside well‐defined research protocols. What does this review add? The pooled PPV of cfDNA testing in screening for MMs was about 40%, ranging from 29% to 91%, for an overall FPR <0.1%. The detection rate and the negative predictive value cannot be determined based on the available evidence because postnatal diagnostic confirmation was not available in the vast majority of fetuses with a low‐risk result, which were more than 99% of all tested cases.